Pengaruh Promosi, Harga, Kualitas Produk, Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Shopeefood - Zuhri, Muhammad Ilham; Lubis, Irsad (Innovative: Journal Of Social Science Research, 2024)
This study aims to investigate how factors such as price, promotion, product quality, and service quality influence consumer decisions when making purchases on the ShopeeFood platform. The research uses a quantitative method with multiple linear regression analysis. The sample consists of 100 respondents from Binjai City, and questionnaires were used as the primary data source. The variables are measured using the Likert scale. Data analysis techniques include determination test, partial testing (t-test), and simultaneous testing (F-test) to draw conclusions. The results indicate that product quality, promotion, price, and service quality have a positive and significant effect on purchasing decisions at ShopeeFood, with an F-test significance value of 0.000. Based on the t-test, the promotion variable has a positive and significant influence with a significance value of 0.000, price also with a value of 0.035, there is a significant positive effect, product quality does not have a significant impact with a significance value of of 0.542, and service quality has shown a significant positive effect with a significance value of 0.000.